Implementation of Kanban and Poka-Yoke to Improve Production Efficiency at CV. XYZ - Nando, Fiky Two; Priyangga, Dharu Zastia; Ramadhani, Akbar; Afnan Fairuz, Ferdian Nizar; Armalia, Aqillah; Putri, Katerina Najwa (Indonesian Journal of Engineering and Technological Innovation, 2025)
XYZ is a household plastic components manufacturer facing elevated defect rates (4–5% daily), accumulation of work-in-process (WIP) in the cooling area, and recurring labeling errors during packaging. This study evaluates the combined application of Kanban as a pull-based material flow control and Poka-Yoke as simple error-proofing devices to improve production efficiency and product quality. A quantitative descriptive approach was employed, using direct observation, time-and-motion measurements, interviews with operators and supervisors, and before–after comparisons of key performance indicators. Kanban sizing was calculated using D = 125 units/hour, L = 4 hours, S = 0.1, and container capacity C = 50 units, yielding an optimal 11 Kanban cards. Poka-Yoke implementations included automatic temperature alarms on molding machines, fixture sensors at finishing stations, and barcode-based label verification at packaging. After implementation, WIP decreased from 280 to 150 units (−46%); inter-process waiting time reduced from 45 to 20 minutes (−56%); daily output increased from 800 to 950 units (+18.7%); defect rate declined from approximately 5% to 1.8%; and labeling errors were eliminated. The results indicate that integrating Kanban and Poka-Yoke can effectively streamline production flow, reduce waste, and enhance productivity in small-to-medium plastic manufacturing operations. Implications, limitations, and recommendations for broader application are discussed.